PERANCANGAN SISTEM INFORMASI PELEPASAN REKAM MEDIS MENGGUNAKAN MICROSOFT VISUAL STUDIO 2012 DI INSTALASI REKAM MEDIS RSUD KABUPATEN SUMEDANG - Moh Yudiyatna Fahmi; Diki Maulana; Falaah Abdussalaam; Erix Gunawan; Neneng Yuniarty (LPSDI Bina Patria, 2023)
This study aims to determine the design description of the Visum et Repertum information system, Medical Resume & Medical Certificate at Sumedang Regional General Hospital. The research methodology used by the author is descriptive qualitative with data collection techniques using observation, interviews, and literature studies to find out the problems faced from the research that has been done and with the waterfall development method. Microsoft Visual Studio 2012 as a programming language and Microsoft Access as a database. Based on the research found several problems as follows: (1) making Visum et Repertum, Medical Resume, and Medical Certificate still using Microsoft Office applications. (2) The process of making Visum et Repertum, Medical Resume & Medical Certificate is long because the DPJP (Doctor in charge of services) is not on duty every day and there is no current technology to make it easier for doctors to fill in and perform their duties related to the release of medical information. Proposing a new system design using a computerized application program specifically for making Visum et Repertum, Medical Resumes, and Medical Certificates to make it easier for officers, speed up the manufacturing process, and reduce the risk of human error, etc. should be done